PENDAMPINGAN KEGIATAN BACA TULIS AL QUR’AN DENGAN METODE IQRO’ DI MADRASAH DINIYAH AR RAHMAN DUSUN DANCE - Imron Rosyadi; Deno Putri Ayu Jingga; Syiva Istianatul Mahbubah; Nuning Isfa’ Nisa’ul Chusnah (JIK-PkM: Jurnal Inovatif dan Kreatif hasil Pengabdian kepada Masyarakat, 2023)
Education is the most important thing in everyone's life. Madrasah diniyah are included in informal education in the field of religion. The problems that arise in the students in the Madrasah diniyah ar-Rahman Dance hamlet are due to the limited conditions of the teachers so that the learning of the Koran is only focused on reading the Koran which is listened to directly by the teacher. This causes the ability of students to read the Qur'an is still relatively low. Therefore, efforts were made to assist reading and writing activities of the Qur'an using the Iqro' method at Madrasah Diniyah Ar-Rahman. The method used in this research is the PAR (Participation Action Research) method using data collection techniques in the form of observation, interviews, and documentation. The results showed that with the assistance of reading and writing the Qur'an, it could improve the ability of the students of Madrasah Diniyah Ar-Rahman in reading and writing the Qur'an properly and correctly. Keywords: Reading and Writing the Qur'an, IQRO Method, Madrasah Diniyah